The Impact of Celebrity Endorsement on Brand Affection and Purchase Intention: The Mediating Role of Word of Mouth - Saleem, Farida (Lahore.j.bus, 2017)
Celebrity endorsement is widely used as an advertising technique. This study examines three dimensions of celebrity endorsement, including trustworthiness, expertise and attractiveness, as predictors of positive word of mouth by consumers. It also gauges the impact of word of mouth on purchase intention and brand affection in terms of the role it plays as a mediating construct between celebrity endorsement and consumers’ behavioral outcomes. The study uses a sample of 369 respondents to test a structural equation model. Its results reveal that the fully mediated model is superior to the partially mediated model and that trustworthiness is the most important attribute of celebrity endorsement, yielding positive consumer behavior.